The Profit Rate as a Measure of Monopoly Power - Bain, Joe S. (Quarterly Journal of Economics, 1941)
The meaning of monopoly, 271. — The problem of measurement, 272. — Theoretical excess profits as indicators of monopoly, 273. — The problem of defining the rate of excess profit, 275. — Definition of the rate for a short fiscal period, 277. — The quantity of assets which a competitive firm will hold, 281. — The relation of the accounting to the theoretical rate of profit, 289. — The accounting profit rate as a measure of monopoly power, 291.